Efeito de nanopartículas de óxido de zinco e do sulfato de zinco no cladócero tropical Ceriodaphnia Silvestrii - Souza, Helena da Silva Viana de (2018)
Zinc is an essential metal for living beings, but can become toxic at high concentrations. Currently, zinc has been used in the industrial production of nanoparticles (NPs), which have been calling attention in the nanotechnological scenario due to their large use in personal hygiene products, cosmetics, paints, fabrics, biosensors and in diagnosis and therapy of several types of cancer. However, the production of NPs on a large scale has raised concerns about the disposal of these nanomaterials in aquatic ecosystems and the consequences for the biota. The objective of this study was to compare the effects of two zinc compounds, zinc oxide nanoparticles (NP-ZnO) and zinc sulfate (ZnSO4), on the tropical cladoceran Ceriodaphnia silvestrii, in order to identify the possible effects on the effective concentration (CE50) in acute exposure tests, and in growth and reproduction in chronic exposure tests, as well as to distinguish whether the main cause of the potential toxicity of NPs is due to the release of zinc ions or their intrinsic properties. Acute tests (control; 0.1; 0.2; 0.3; 0.4; 0.5 and 1.0 mg L-1 for NP-ZnO and control 0.032; 0.1; 1.04 and 3.35 mg L-1 for ZnSO4) lasted 48 hours and the chronic ones (control; 0.006; 0.0125; 0.025; 0.05 and 0.1 mg L-1 for NP-ZnO and control; 0.006; 0.01; 0.02; 0.04 and 0.09 mg L-1 for ZnSO4), 8 days. The EC50-48h for NP-ZnO was 0.35 mg L-1, while the EC50-48h for ZnSO4 was 0.92 mg L-1. In the chronic tests, there was a significant reduction of the mean body size of 11.3% in the treatment of 0.1 mg L-1 of NP-ZnO and 10% in the treatment of 0.01 mg L-1 of ZnSO4; reduction in the mean number of accumulated eggs and neonates produced per female of 53.9% and 72.5% for NP-ZnO, and 55% and 50% for ZnSO4, respectively. Effects of bioaccumulation and absence of egg hatching (abortion) on the highest concentrations evaluated for NP-ZnO were also observed. Our results showed acute and chronic toxic effects by exposure of C. silvestrii to NP-ZnO and ZnSO4. Chronic exposure affected microcrustacean growth and reproduction parameters at concentrations of 0.006 mg L-1 for both substances, with toxicity coming from both free metal ions and the properties of NPs. Therefore, the present work can subsidize studies and regulations aimed at the management and disposal of NP-ZnO and ZnSO4 in freshwater environments.